A 5-day-old-newborn with a large right upper eyelid coloboma - Zhang, Dalia V.; Chundury, Rao V.; Blandford, Alexander D.; Perry, Julian D. (Digital Journal of Ophthalmology, 2017)
A 5-day-old girl presented to the Cleveland Clinic Cole Eye Institute Oculoplastics service for evaluation of right eye exposure. She was born at full term by spontaneous vaginal delivery after an uncomplicated pregnancy. Family history was unremarkable for any known heritable conditions or ocular disease.